The curative effects of the traditional Chinese herbal medicine "Jinchuang ointment" on excisional wounds - Tsung-Jung Ho; Jhong-Kuei Chen; Tzong Shiun Li; Jung-Hsing Lin; Yung-Hsiang Hsu; Jia-Ru Wu; Wan-Ting Tsai; Hao-Ping Chen (BMC, 2020)
Abstract Background "Jinchuang ointment" is a traditional Chinese herbal medicine for external incised wounds. This herbal medicine has been successfully used to treat patients with diabetic foot ulcers and pressure sores in Taiwan for several decades. We previously examined its biological activities on cell-based in vitro assay platforms. Because some patients refused to use animal-derived ingredients ointment during our clinical practice, the efficacy of plant oil-based reconstituted "Jinchuang ointment" was also investigated. Methods A porcine excisional wound model was established and used to evaluate its efficacy in vivo in this study. Besides, an unusual clinical case is also present. Results As judged from the wound appearance of animal studies on day 14 and the results of blood flow flux at the wound sites on day 28, "Jinchuang ointment" accelerated wound closure significantly better than the control group. Conclusions The results from clinical treatment, histopathological evaluation, and the animal study showed that "Jinchung ointment" promotes wound healing significantly better than the control group. Also, sesame oil-reconstituted ointment can be a choice for patients who refuse to use lard-containing ointment.